The role of miRNA genes participating in VHL-HIF1α in clear cell renal cell carcinoma - V. N. Pavlov; I. R. Gilyazova; A. A. Izmailov; E. A. Klimentova; I. R. Sultanov; M. A. Bermishev; Z. R. Akhmadeev; A. Kh. Nurgalieva; G. V. Ishbulatova; E. K. Khusnutdinova (Вестник урологии)
Introduction. Much attention in ccRCC development is paid to VHL-HIF1α pathway genes. Numerous genes involved in the pathogenesis of ccRCC are targets for miRNA. Alteration in the nature of interaction with miRNA binding site as a result of a single nucleotide substitution may promote change the expression of target genes involved in the genesis and development of tumors.Purpose of research. Analysis of the role of polymorphic variants in the miRNA binding sites of the VHL-HIF1α gene pathways in ccRCC development.Materials and methods. We used 225 DNA samples isolated from the venous blood of ccRCC patients who are hospitalized to the Clinic of the Bashkir State Medical University, and 298 healthy individuals. The genotyping of miRNA binding site polymorphisms in VHL-HIFα-dependent pathway genes (rs10982724 of the DEC1 gene, rs406271 of the TFRC gene, rs10491534 of the TSC1 gene, rs1642742 of the VHL gene, rs3025033 of the VEGFA gene) was performed using Taq-man assays.Results. The frequency distribution of alleles and genotypes of rs1642742 of the VHL gene showed that rs1642742 *GG is a marker of the increased risk for ccRCC. In addition, rs10491534 * C allele was found to be the marker for severe ccRCC (p = 0.044; OR = 1.72 (CI = 1.012-2.911)), and rs10491534 * TT genotype (p = 0.044; OR = 0.55; (95% CI = 0.31–0.98)) of the TSC1 gene was shown to be a protective marker for ccRCC of severe duration.Conclusions. The study indicated the association of miRNA binding sites polymorphisms with the risk of ccRCC development and severity of disease. However, further studies of the genes are needed to establish their functional significance and role in the pathogenesis of ccRCC.